Expert Validation of a Medication Error Assessment Tool in the Integrated Medicine Management Model for Geriatric Patients with CHF - Welinda Dyah Ayu; Umi Athiyah; Elida Zairina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Geriatric patients with congestive heart failure (CHF) face an elevated risk of medication errors due to physiological changes, polypharmacy, and comorbidities. Integrated Medicine Management (IMM) is a multidisciplinary model designed to minimize drug-related problems through structured interventions during admission, hospitalization, and discharge. This study aimed to validate a medication error checklist developed for the IMM model, specifically for hospitalized older adults with CHF. A descriptive, quantitative design was applied, with expert-based content validation. A purposive sample of eight healthcare professionals, including physicians, clinical pharmacists, and senior nurses, was recruited. Each checklist item was assessed for relevance using a 4-point Likert scale. Content validity was evaluated using the Item-Level Content Validity Index (I-CVI) and the Scale-Level CVI (S-CVI/Ave). All nine items obtained I-CVI values of ≥0.875, with seven items achieving a full consensus (I-CVI = 1.00). The overall S-CVI/Ave was 0.97, indicating excellent content validity. The checklist integrates global safety frameworks, including the STOPP/START criteria, the WHO Medication Without Harm initiative, ISMP's high-alert medication guidance, and The Joint Commission's reconciliation protocols. Core components address reconciliation, therapy duplication, high-risk drugs, and discharge education. The validated checklist demonstrates strong content validity and clinical relevance for detecting medication-related problems in hospitalized geriatric CHF patients. Integration into digital platforms such as MINE (Medicine IN gEriatric) may enhance interprofessional collaboration, reduce preventable errors, and promote safer pharmacotherapy across care transitions.